2016
DOI: 10.1002/lsm.22454
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pigmentary disorders in patients with skin of color with a novel 755 nm picosecond, Q‐switched ruby, and Q‐switched Nd:YAG nanosecond lasers: A retrospective photographic review

Abstract: The 755 nm alexandrite picosecond, 694 nm ruby, 532 nm, and 1064 nm neodynium:YAG nanosecond lasers appear to be safe and effective modalities for removal of pigmentary disorders in skin of color patients with no long-term complications if used appropriately. This study demonstrates the potential of the 755 nm alexandrite picosecond laser in further clinical applications beyond tattoo removal. While the Q-switched lasers were effective, promising results were also observed using an early version of the novel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 13 publications
3
77
0
5
Order By: Relevance
“…This gives the opportunity for safer and more effective treatment options for darker Fitzpatrick skin types without the significant risks of thermal diffusion to the surrounding tissues and possible post‐inflammatory hyperpigmentation (PIH) that nanosecond pulse durations can produce. There are numerous studies published to support this .…”
Section: Introductionmentioning
confidence: 84%
“…This gives the opportunity for safer and more effective treatment options for darker Fitzpatrick skin types without the significant risks of thermal diffusion to the surrounding tissues and possible post‐inflammatory hyperpigmentation (PIH) that nanosecond pulse durations can produce. There are numerous studies published to support this .…”
Section: Introductionmentioning
confidence: 84%
“…and Chan et al . reported the successful application of PSAL for the treatment of naevus of Ota . It was observed that fewer treatment sessions were required by PSAL to achieve comparable clinical efficacy compared with Q‐switched lasers .…”
mentioning
confidence: 99%
“…4,8,9 Embora não exista tratamento padrão para o LPP, 10 há relatos de uso de corticóide oral e tópico, tacrolimus tópico de forma isolada ou associado à dapsona, e também de Q--switched (QS) laser. 5,7 O uso de lasers QS são promissores, mas com resultados variados. Em 2015 6 Yates et al, compararam o uso dos lasers QS alexandrita, QS Nd-YAG 1064, e QS KTP no tratamento de lesões perioculares, como nevo de Ota e tatuagem, 11 sendo os melhores resultados alcançados com QS Nd-YAG 1064.…”
Section: Discussionunclassified
“…[2][3][4] A etiologia da doença é indeterminada, havendo relato de possível associação com antígenos que causariam reação liquenóide e também exposição a radiação ultravioleta (RUV) ou agentes fotossensibilizantes. 5,6 Embora alguns estudos tenham apontado para forte correlação entre o vírus da hepatite C e LPP, sobretudo do ponto de vista epidemiológico, esta não foi confirmada por outros autores, necessitando de investigação adicional.…”
unclassified